Novel Biomarkers for Heart Disease - Lichtenauer, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cardiac biomarkers such as troponins and natiuretic peptides have made a great impact on clinical decision making as well as improving our understanding of molecular mechanisms of different disease conditions. However, the biomarkers that are currently in use do not reflect all the multiple disease pathways that are involved in a broad spectrum of cardiac disease conditions ranging from acute coronary syndrome, to heart failure (and heart failure with preserved ejection fraction, HFpEF), to pulmonary hypertension or arrhythmias. In this Special Issue, we will provide an overview of the current developments in the field of biomarker research, beginning with research on molecular pathways and cellular communication (e.g., microRNA) up to the clinical use of biomarkers.